The Analysis Of English Teacher Barriers On Teaching English Through Kahoot: ELT Teacher Experiences - Prayudha.S, Joko (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
The integration of technology in classroom activities can provide innovation in the learning process. The teacher should use the proper technology or learning platform that can attract students motivation in learning activities so that students can improve their understanding of the materials being taught. There are many technologies or learning platforms that teachers can implement in the learning process; one of those is the Kahoot learning platform. This research is conducted to find out the barriers faced by English teachers when implementing the Kahoot learning platform during English learning activities in the classroom. This research used a qualitative through descriptive approach. The informants in this research are three English teachers who implemented the learning process by using the Kahoot learning application. The data was collected through observation, a questionnaire, and an interview to know how barriers occurred in the learning process during the use of the Kahoot application. The data was analyzed through data reduction, data display, and conclusion. The results showed that there are some barriers that teachers face during the implementation of the learning process through the Kahoot learning application. They are: 1) student technology; 2) student interest; 3) preparation; 4) clear instruction; and 5) time management.